Pelaksanaan Pembelajaran Bahasa Indonesia Bagi Anak Tunagrahita Ringan Kelas VII di SLB Al-Azhar Bukittinggi - Aprianti, Nisa (RC-INSTITUT, 2019)
This research describe to how implementation Indonesian Learning conducted by the teacher Y on class VII in the SLB Al-Azhar Bukittinggi and what are the obstacles experienced by the teacher Y when teaching and how teacher?s efforts in overcoming these obstacles. This research is motivated by the success of the teacher Y creates and running a learning program for mentally retarded children last year. Teacher Y programmed his students in their inventions reading poetry and succes that sure by the results of students work that has been recorded by the teacher Y. Not only students who are active in writing, but the teacher Y are also very active in writing literature and that was also proven by the many works of teacher Y that has been recorded. But this year the teacher Y experienced difficulties in the process Indonesian Learning because students who teach teacher Y are very diverse. The students consists of students with mental retardation, hearing impairment and visual impairment. By using the case study method and qualitative descriptive approach, this research  can be focuses on the implementation of Indonesian language learning conducted by the taecher Y as it is. The subject of this research were the teacher Y who taught in class VII. The process of collecting proof in this research is done through observation, interviews and documentation studies.